ORFV infection enhances CXCL16 secretion and causes oncolysis of lung cancer cells through immunogenic apoptosis - Ruixue Wang; Jingying Mo; Xiaoshan Luo; Guixian Zhang; Fang Liu; Shuhong Luo (Frontiers in Cellular and Infection Microbiology, 2022)
Oncolytic viruses have been emerging as a promising therapeutic option for cancer patients, including lung cancer. Orf virus (ORFV), a DNA parapoxvirus, can infect its natural ungulate hosts and transmit into humans. Moreover, the ORFV has advantages of low toxicity, high targeted, self-amplification and can induce potent Th1-like immunity. This study explored the therapeutic potential of ORFV infection for human lung cancer therapy and investigated the molecular mechanisms. We used a previously described ORFV NA1/11 strain and tested the oncolysis of ORFV NA1/11 in two lines of lung cancer cells in vitro and in vivo. Treatment of both cell lines with ORFV NA1/11 resulted in a decrease in cell viability by inducing cell cycle arrest in G2/M phase, suppressing cyclin B1 expression and increasing their apoptosis in a caspase-dependent manner. The ORFV NA1/11-infected lung cancer cells were highly immunogenic. Evidently, ORFV NA1/11 infection of lung cancer cells induced oncolysis of tumor cells to release danger-associated molecular patterns, and promoted dendritic cell maturation, and CD8 T cell infiltration in the tumors by enhancing CXCL16 secretion. These findings may help to understand the molecular mechanisms of ORFV oncolysis and aid in the development of novel therapies for lung cancer.